2012
DOI: 10.1002/jnr.23023
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, effective, and long‐lasting behavioral recovery produced by microsutures, methylene blue, and polyethylene glycol after completely cutting rat sciatic nerves

Abstract: Behavioral function lost in mammals (including humans) after peripheral nerve severance is slowly (weeks to years) and often poorly restored by 1-2-mm/day, nonspecifically directed outgrowths from proximal axonal stumps. To survive, proximal stumps must quickly repair (seal) plasmalemmal damage. We report that, after complete cut- or crush-severance of rat sciatic nerves, morphological continuity, action potential conduction, and behavioral functions can be consistently (>98% of trials), rapidly (minutes to da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
185
3
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(210 citation statements)
references
References 47 publications
19
185
3
3
Order By: Relevance
“…The ability to immediately regain nerve function after injury to a segment of a peripheral nerve would revolutionize current nerve repair strategies. We have previously described a technique that allows early physiologic and behavioral recovery after nerve transection by fusing the cut ends of the axons back together with the hydrophilic polymer, polyethylene glycol (PEG) [4]. We then expanded that strategy and the current report describe how both physiologic and behavioral recovery can be immediately restored across a nerve gap using a fresh nerve autografts and this PEG fusion technique [29].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to immediately regain nerve function after injury to a segment of a peripheral nerve would revolutionize current nerve repair strategies. We have previously described a technique that allows early physiologic and behavioral recovery after nerve transection by fusing the cut ends of the axons back together with the hydrophilic polymer, polyethylene glycol (PEG) [4]. We then expanded that strategy and the current report describe how both physiologic and behavioral recovery can be immediately restored across a nerve gap using a fresh nerve autografts and this PEG fusion technique [29].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have been promising demonstrating a small improvement in gait function after nerve crush injury (axonotmesis) and a 13-fold improvement after neurotmesis injury, compared to standard of care microsurgery [70, 71]. A recent study reported that compound action potentials could be recorded distal to a 10-mm nerve graft repair up to 7 days after surgery [72].…”
Section: Translational Research In Peripheral Nerve Repairmentioning
confidence: 99%
“…A specific sequence of antioxidases and polyethylene glycol has now been developed to lead to optimal axonal fusion. 53 This study demonstrated almost immediate restoration of electrophysiology (compound action potentials) across the repair site following fusion as well as dramatic improvement in functional recovery (gait function) in a rat model of sciatic nerve repair when polyethylene glycol fusion was used. This repair method was recently used in humans for the first time, in digit re-implantation, with positive results, but requires further clinical study to determine its long-term efficacy and widespread application.…”
Section: Polyethylene Glycol Fusionmentioning
confidence: 68%